(untitled) (Applied Biological Research, 2024)
Vitamin D, which is either produced in the skin upon sunlight exposure or acquired through diet, plays an important role in calcium hemostasis and bone remodeling. Vitamin D deficiency is a global issue and awareness about its importance has brought a tendency to use its supplements worldwide. The present study was aimed to assess the use of vitamin D supplementation among the general population in Hail region of Saudi Arabia. The data from 377 subjects was analyzed. The study revealed that 40.31% of participants used supplements. Importantly, 18.42% individuals were using supplementation without knowing the vitamin D level. On the other hand, several participants with low level were not using supplements, while some with normal or even high level reported using supplements. A significant difference was observed for knowing vitamin D level in supplement consumers versus others at p value <0.05. Excessive supplementation is risk for development of side effects. There is a need to be cautious with artificial supplements as their long-term effects are not fully known. Thus, dietary sources and basking in sunlight should be preferred unless there is a strong clinical indication to start supplementation.